Problems and prospects of red mud utilisation - Prasad P.M.; Subramanian S. (My University, 2025)
A general survey is presented on the generation and characteristics of Red Muds. The interrelationship between Mud properties, their disposal and utilisation is emphasised. After an outline on the possible applications for Red Muds, the problems related to. important (potential) uses have been pointed out. Suggestions have been incorporated on what needs to be done to promote the utilisation of Red Muds particularly in the Indian context.